LEGAL PROTECTION AND PUBLIC SERVICES FOR ACCESSIBILITY OF PERSONS WITH DISABILITIES IN EDUCATION - Ratnaningsih; Titis Srimurni; Titik Sriastutik; M. Akmal Naufaldi Maulidandi (Awang Long Law Review, 2025)
Education plays a fundamental role in a human's life. As one of the state goals, education is stated in the preamble of the 1945 Constitution, Paragraph 4, namely to educate the nation's life. Everyone has the right to receive education, however its implementation is never easy, especially for the disabled people. Persons with disabilities have rights to proper accommodation, dignified public services without discrimination, assistance, translation, and free access to facilities in public service places. The constitutional right to education for disabled people is regulated in article 10 of Act Number 18 of 2016 concerning People with Disabilities, and Government Regulation Number 13 of 2020 concerning Reasonable Accommodation for Disabled learners. The current inclusive school policy is limited and not supported by adequate services and teachers. The inability of students to understand such conditions may cause bullying and create a wall of separation for people with disabilities to be able to get an equal education. Empirical juridical field research was conducted at the Association of People with Disabilities in Lumajang Regency to investigate the legal protection of disabled rights and accessibility to public services. The result shows that legal protection for disabled people is not optimally implemented since there have not been properly installed disabled-friendly public services. Thus, legal certainty, disabled-friendly public services, the availability of facilities, educators, and acceptance of disabilities are crucial for achieving equality in education without discrimination. To achieve difable equality in education without discrimination, it needs to establish regulations with legal certainty, provide disabled-friendly public services related to the availability of facilities and infrastructure, the availability of educators with special expertise in disabilities, and prepare the mental acceptance of other students with disabilities in their educational institutions.